Investigation and comparison of adherence- and biofilm-forming capacities of yellow-pigmented Chryseobacterium, Elizabethkingia and Myroides spp. isolated from South African aquaculture systems - Jacobs, Anelet (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.